Application of the Picture and Picture Learning Model to Increase Low Class Students' Interest in Learning - Zulyadain, Ahmad; Dimansyah, Athalia; Ramadhani, Nabila Aulia (Journal of General Education Science, 2023)
The application of innovative learning models as an effort to improve the learning process is very enjoyable, thereby increasing students' interest in participating in the implementation of learning. The use of learning models in learning activities is important. A teacher must choose the right learning model so that the teaching and learning process meets the desired goals. However, in reality teachers still tend to use conventional learning models so that students become less interested and become inactive in participating in learning, even though interest is one of the factors that influences student learning success. Therefore, the model that can be used as a solution to this problem is the picture and picture learning model. This research was carried out at SD Negeri 050724 which is located at Jl. T. Amir Hamzah Kel. Pekan Tanjung Pura District. Tanjung Pura, Kab. Step up. In this research, the PTK (Classroom Action Research) type of research was used. Data collection techniques used were observation, questionnaires and tests. The subjects in this research were all class I students at SD Negeri 050724, totaling 16 people. The object of this research is to increase student interest and learning outcomes through the use of the picture and picture learning model.